Clinical, electromyographical, histopathological characteristics of COVID-19 related rhabdomyolysis. (December 2020) - Rosato, Chiara; Bolondi, Giuliano; Russo, Emanuele; Oliva, Alessandro; Scognamiglio, Giovanni; Mambelli, Emanuele; Longoni, Marco; Rossi, Giulio; Agnoletti, Vanni
Rhabdomyolysis is an uncommon complication of the coronavirus disease 2019 (COVID-19) infection. Previous reports have described its management and treatment in medical units, but have not discussed confirmatory tests or differential diagnosis. We report a case of a 58 year-old male patient, who was admitted for COVID-19 pneumonia and subsequently developed severe weakness, inability to move limbs, acute renal failure, significantly elevated myoglobin and creatinine kinase, and was diagnosed with rhabdomyolysis. Continuous renal replacement therapy, the treatment modality of choice over hyperhydration due to ongoing mechanical ventilation, was effective in resolving symptoms. No direct viral invasion of muscles was noted on biopsy. Here, we describe his symptoms, electromyography, and muscular biopsy results, and further discuss the possible differential diagnoses. Neuromuscular symptoms related to COVID-19 require careful clinical analysis. In addition, detailed reports of patients' course of illness and diagnoses will assist in improving care for affected patients.